Exploring Elementary Students’ Motivation in English Vocabulary Learning through Wordwall: A Qualitative Study - Asih Rosnaningsih; Peni Astuti (Foremost Journal, 2026)
Digital technology has increasingly become an important component of English language learning in elementary schools. This qualitative study explores elementary students’ motivation in learning English vocabulary through Wordwall at SD Daan Mogot 1 Tangerang City, involving 27 third-grade students selected through purposive sampling. The study focuses on students’ experiences, engagement, responses, and perceptions during Wordwall-based vocabulary learning. Data were collected through classroom observations, semi-structured interviews with selected students and the English teacher, and documentation. The data were analyzed thematically through data condensation, data display, and conclusion drawing. The findings indicate that Wordwall created a more interactive and enjoyable learning environment that encouraged students to participate actively, respond to questions, and practice vocabulary repeatedly. The findings also suggest that Wordwall supported students’ enjoyment, attention, participation, confidence, and learning interest. The study concludes that Wordwall can serve as a supportive digital medium for fostering elementary students’ motivation in English vocabulary learning when integrated with appropriate teacher guidance and pedagogical strategies.